An Improved Flood Forecasting Model of the Blue Nile River in Sudan (University of Khartoum Engineering Journal, 2022)
Reliable flood predictions with a reasonable lead time in the Blue Nile River in Sudan are vitally important to avoid catastrophic damages due to flooding of this river and the main River Nile. A HEC-RAS model was initially applied to the Blue Nile by representing the river as a single reach. The resulting original model was subsequently improved by including the two tributaries of the river, Rahad and Dindir, and also the two existing reservoirs, Rosaries and Sinnar, to the model. The original and the improved models were calibrated using 1988 flood data for the period from June to September inclusively. Then they were validated using flood data of 2009 and 2010 for the same period. The results clearly show the remarkable performance of the improved HEC-RAS model compared to the original HEC-RAS model. This also suggests that the complex behaviour of the Blue Nile River during floods cannot be only modelled by a simple model such as the original HEC-RAS model but it requires a more sophisticated model such as the improved HEC-RAS model. The improved HEC-RAS model can be used by the authorities to issue flood warnings to the affected areas before ample time to allow for proper preparedness.